2002
DOI: 10.1254/jjp.88.119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral OPC-28326, a Selective Femoral Arterial Vasodilator, on Hindlimb Subcutaneous Tissue Temperature in Conscious Dogs Under Buprenorphine Sedation

Abstract: ABSTRACT-In dogs, rectal temperature was decreased to about 36°C at 2 to 2.5 h after sedation with buprenorphine (0.3 mg/body, i.m.), and hindlimb subcutaneous tissue temperature (T SC) in the thigh decreased in a similar manner. TSC in the dorsum of the foot showed a greater decrease than that in the thigh. OPC-28326 (4-(N-methyl-2-phenylethylamino)-1-(3,5-dimethyl-4-propionyl-aminobenzoyl) piperidine hydrochloride monohydrate) at doses of 0.3, 1.0 and 3.0 mg/kg, p.o. inhibited the buprenorphine-induced decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Activation of m -opioid receptor in brain has also been shown to mediate the fever response in rats (18 -21). Furthermore, a more recent report showed that the rectal temperature of dogs was decreased to about 36°C at 2 to 2.5 h after sedation with intra-muscular administration of buprenorphine (22). This raises the additional possibility that buprenorphine has an antipyretic action.…”
Section: Introductionmentioning
confidence: 98%
“…Activation of m -opioid receptor in brain has also been shown to mediate the fever response in rats (18 -21). Furthermore, a more recent report showed that the rectal temperature of dogs was decreased to about 36°C at 2 to 2.5 h after sedation with intra-muscular administration of buprenorphine (22). This raises the additional possibility that buprenorphine has an antipyretic action.…”
Section: Introductionmentioning
confidence: 98%
“…OPC‐28326 (4‐[N‐methyl‐2‐phenylethyl‐amino]‐1‐[3,5‐dimethyl‐4‐propionyl‐aminobenzoyl] piperidine hydrochloride monohydrate), a piperidine derivative, is a selective α‐adrenergic antagonist with preferential binding to the α 2C ‐AR subtype (α 2C is several‐fold stronger than α 2B , followed in decreasing strength by α 2A and α 1 ) (4–6). Animal studies involving OPC‐28326 have demonstrated improved hind‐limb blood flow during cold exposure and normalized skin temperature under anesthesia with this drug (6, 7). OPC‐28326 has been administered to patients with atherosclerotic peripheral vascular disease and is well tolerated in single doses up to 240 mg.…”
mentioning
confidence: 99%
“…OPC-28326 acts as an ␣ 2 -adrenoceptor antagonist, showing the highest affinity for the ␣ 2C -adrenoceptor subtype (28,34). In addition, an earlier study reported that in an ischemic leg model OPC-28326 also exerted angiogenic effects via the Akt/endothelial nitric oxide synthase (eNOS) pathway (33).…”
mentioning
confidence: 99%